Sistema para avaliação de desempenho e calibração de sensores de gases de baixo custo aplicados ao monitoramento da qualidade do ar - Gamboa, Vanessa Schwarstzhaupt (2021)
The increasing emissions of air pollutants have been a current issue and with great interest by regulatory agencies, industries and society in general, as they represent a threat to health and the environment. Therefore, it is imperative to estimate the concentration of these compounds in the atmosphere in order to keep them at the safe levels required by regulatory authorities. Monitoring with the use of low-cost atmospheric sensors has been an emerging alternative and with great perspective of use to complement the data obtained by traditional air quality monitoring stations. However, the data obtained by these low-cost sensors are still questionable and can often be unreliable. Thus, the objective of this work was to build an system for calibration and evaluation of performance parameters of low-cost sensors, comparing their results to reference analyzers. In this sense, three low cost sensors for CO, O3 and SO2 of the DR1000L monitor (Scentroid) were calibrated and evaluated against the performance parameters defined by Baseline drift, linearity, precision, bias, accuracy, response time, interference from polluting gases, long-term drift and temperature interference. There were no significant deviations from baseline drift for any sensor. All sensors had a linear profile, good accuracy and a response time of less than 2 minutes. After calibration, satisfactory accuracy and bias data were obtained. The SO2 sensor showed signal disturbances in the presence of different concentrations of CO. Long-term drift suggests a calibration period of less than 60 days. Temperature is directly related to sensitivity variations in low-cost sensors. In general, the use of these sensors for monitoring air quality is suggested when their performance parameters are properly known and their sensors are properly calibrated.